The ANALYSIS OF HOUSEHOLD ASSETS ON LIVELIHOOD STRATEGIES OF SMALLHOLDER CROP FARMERS IN FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA. - Enagi, I.M (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
The study analyzed the effects of household assets on livelihood strategies of smallholder food crop farmers in the Federal Capital Territory, Abuja, Nigeria. Multistage sampling technique was employed to select 68 smallholder crop farmers from three Area Councils in the Territory using questionnaire to solicit for primary data from the respondents. Descriptive statistics and multinomial logit analysis were used to analyze the data. Results of the analysis reveals that smallholder crop farmers were within the age range of (41-50%). They were mostly males (77.94%) and married 98.53%. Their level of education was primary school education (38.24%) with farming experience of (21-30years). They were mostly (6-10) members/household. Farmers in FCT carried out LS1 (17.5%), LS2 (26.47%), LS23 ( 19.22%) and LS4 (36.76%). Results of household assets on livelihood strategies shows that distance from home to all season road was significant on LS1 at 5% level of significance (1.97)** as well as LS2 at 10% (2.01)** respectively. Income was significant at 1% (-3.03)***. It was therefore recommended that more household assets should be utilized among smallholder crop farmers. f the analysis reveals that smallholder crop farmers were within the age range of (41-50%). They were mostly males (77.94%) and married 98.53%. Their level of education was primary school education (38.24%) with farming experience of (21-30years). They were mostly (6-10) members/household. Farmers in FCT carried out LS1 (17.5%), LS2 (26.47%), LS23 ( 19.22%) and LS4 (36.76%). Results of household assets on livelihood strategies shows that distance from home to all season road was significant on LS1 at 5% level of significance (1.97)** as well as LS2 at 10% (2.01)** respectively. Income was significant at 1% (-3.03)***. It was therefore recommended that more household assets should be utilized among smallholder crop farmers.